Small-Scale Soft-Sediment Deformation Structures in the Cross-Bedded Coconino Sandstone (Permian; Arizona, United States); Possible Evidence for Seismic Influence - Brand, Leonard; Maithel, Sarah (Frontiers in Earth Science, 2021)
Abstract The Permian Coconino Sandstone of northern Arizona contains numerous small-scale, soft-sediment deformation structures (SSDSs). These novel structures may be indicators of paleoenvironment or sedimentary processes. These SSD are generally shallow and occur on the surfaces of cross-beds, in contrast to convoluted bedding up to tens of meters thick commonly observed in some other eolian sandstones. These differences in structures imply differences in the processes that formed the Coconino Sandstone, or differences in the underlying depositional conditions. These SSDSs occur in outcrops at the Grand Canyon, and farther south in quarries near the towns of Seligman and Ash Fork. Size, orientation, structure, sedimentary context, clay content, and porosity of the structures are described. The SSDSs occur as small folds and ridges on the paleo lee side of otherwise undisturbed cross-beds. Some are associated with small rotated sandstone blocks within the cross-beds. The structures are exposed on bedding plane surfaces and in cross-section on vertical quarry walls. A few SSDSs up to a meter thick also occur in the Coconino Sandstone, but the others are only up to a few cm thick, 2-10 cm wide, and 20 cm to 10 m long. Evidence is presented that liquidization (as fluidization or liquefaction) may have been involved in producing these features, implying a high water content in scattered locations at time of deformation, but this process also requires some stressor to trigger the deformation. Seismic events may provide a triggering mechanism. The Coconino Sandstone SSDSs represent unusual or previously overlooked small-scale features related to individual foreset surfaces.